SOSIAL EKONOMI BUDAYA KELUARGA BURUH KILANG SAGU DESA TENAN KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI - Miswan, M.; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted in Tenan Village, Tebing Tinggi Barat Barat District, Meranti Islands Regency. The purpose of this study is to describe the socio-economic culture life of sago refinery workers and their contribution to family life. As well as to find out how rational the social actions of sago refinery workers working at the sago refinery. The research subjects or respondents involved in this study were 5 local people who worked at the sago refinery, this study used a descriptive qualitative approach. The main data collection tool is the researcher himself, because the researcher acts as the main instrument in the field. Respondents were chosen based on their ability and openness to selective data search. The method used is observation, documentation and in-depth interviews. Checking data from various sources is done through triangulation techniques in an effort to increase researchers' understanding of what has been discovered. The results of this research indicate that there are four factors that cause a person to become a sago refinery worker, namely: (a) not having special skills; (b) pressured by the economy; (c) no other work; and (d) as additional income. 3) The total income of sago refinery workers is between Rp 2,400,000 - Rp 2,700,000 per month, this income is relatively low but can contribute to his family.Â Keywords: Sago Refinery Workers, Phenomena, Socioeconomic.Â